Implementasi Manajemen Mutu dalam Meningkatkan Mutu Kinerja Tata Usaha SDN No.1 Dompu - Wahyuni, Sri; Mansyuri , M. Ikhwan; Sumarni, Sumarni (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This research aims to determine the implementation of quality management in improving the quality of administrative performance of SDN NO 01 DOMPU. The research method used in this research is qualitative research, with a descriptive approach. Generally, qualitative data collection techniques in this research that are often used by social researchers include; observations, interviews and literature studies or library studies (documentation) to SDN NO 01 DOMPU. The informants consisted of the school principal, head of administration, administrative staff and teachers. Based on the research results, strategies are needed to increase administrative knowledge and competence. The general results of the research are that SDN NO 01 DOMPU has implemented quality management to improve the quality of administrative performance very well, covering several aspects such as leadership, management, curriculum, learning, evaluation and cooperation, but training, development, workshops and seminars are still needed, as well as monitoring all administrative equipment or staff within SDN NO 01 Dompu to improve the quality of administrative performance